Optimizing LNG efficiency by implementing reliquefaction technology to reduce boil-off gas and enhance profitability - Muhtadi, M. Zaky; Rayazen, Ichsan; Istiningrum, Andian Ari; Sugito, Bambang (Politeknik Negeri Lhokseumawe, 2024)
Run an analysis of this abstract, focusing on its relevance, format, flow, and coherence. Technological advancements compel companies to enhance the efficiency of their business operations, including those in the oil and gas sector. Natural gas, particularly Liquefied Natural Gas (LNG), is a vital commodity in significant demand. A primary challenge within the LNG supply chain is minimizing the losses caused by gas evaporation (boil-off gas) during distribution and reception. This study proposes the implementation of a reliquefaction plant on a 170,000 m³ Floating Storage and Regasification Unit (FSRU). Through this innovative approach, this study aims to optimize the utilization of Boil-off Gas (BOG) and augment the company's revenue. The results indicate that the liquefaction plant can reduce BOG by 77 percent, significantly outperforming conventional methods. The economic feasibility analysis revealed a Net Present Value (NPV) of 82,892,970 and an Internal Rate of Return (IRR) of 25 percent, suggesting substantial profit potential. Furthermore, the reliquefaction of 1,777.6 MMBtu BOG per day could potentially increase the company's revenue by IDR 94,078,421,500 annually, surpassing initial estimates. This study contributes significantly to the advancement of more efficient LNG management technologies, providing concrete solutions to minimize energy waste and enhance profitability within the LNG industry. These findings facilitate the implementation of similar technologies at other LNG facilities, potentially transforming industry-wide practices.